SOME PLANKTONIC FORAMINIFERA FROM THE GULF OF MANNAR - Hamsa, K M S Ameer; Nammalwar, P (Indian Journal of Fisheries, 2011)
Studies ’Of p an tonic for,aminifexa in deep se:a floor hav’e been made by Stabbings (1939), Cushman and Henbest (1940) and Wiseman: and Ovey (1950). Our knowledge .on the ptanktonic foraminifera in Indi1an watexs is very me:agre l thOUgh consider,able work !has been doOne .on tihesystemaJtics. l’he pres,ent paper recQrds :sev,en species of planktonic foram nifera for the fuist time from Indian waters. 1’he material used in this study was coHooted at a depth of 180 fatihoms off Mandapam, Gulf of Mannar